The Influence of Changes to Earthquake Regulations SNI 1726:2019 on the Performance of Shop House Structures in North Sumatra - Sitompul, Mizanuddin; Erwin, Syiril; Tobing, Palghe; Kusumadi; Zulkarnain, Fahrizal (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Procedures for planning earthquake resistance for building and non-building structures, SNI 1726:2019 have been approved as a revision of procedures for planning earthquake resistance for building and non-building structures, SNI 1726:2012. With the implementation of SNI 1726:2019, existing buildings should be re-evaluated for their safety against this new regulation. This research examines changes in the performance of shophouse structures in the cities of Sidikalang, Tarutung, Padangsidimpuan, Sei Rampah, Tebing Tinggi, Limapuluh, and Lubuk Pakam. The results show that as a result of the change from SNI 1726:2012 to SNI 1726:2019 there was an increase in the value of the base shear force in the cities of Sidikalang, Sei Rampah, Tebing Tinggi, Limapuluh, and Lubuk Pakam with values respectively 32%, 8%, 11%, 7 %, and 10%. However, in the cities of Tarutung and Padangsidimpuan there was a decrease in the basic shear force value of 3% and 30%. The increase in base shear force is directly proportional to the increase in drift and interstory drift. The interstory drift that occurs is still below the permitted interstory drift.